HCV Kinetic Models and Their Implications in Drug Development. (17th April 2015) - Nguyen, THT; Guedj, J
<x xml:space="preserve">Abstract</x> Chronic infection with hepatitis C virus (HCV) affects about 170 million people worldwide and is a major cause of liver complications. Mathematical modeling of viral kinetics under treatment has provided insight into the viral life cycle, treatment effectiveness, and drugs' mechanisms of action. Here we review the implications of viral kinetic models at the different stages of development of anti‐HCV agents.